2019
DOI: 10.1152/japplphysiol.00048.2019
|View full text |Cite
|
Sign up to set email alerts
|

Different contributions from lungs and chest wall to respiratory mechanics in mice, rats, and rabbits

Abstract: Changes in lung mechanics are frequently inferred from intact-chest measures of total respiratory system mechanics without consideration of the chest wall contribution. The participation of lungs and chest wall in respiratory mechanics has not been evaluated systematically in small animals commonly used in respiratory research. Thus, we compared these contributions in intact-chest mice, rats, and rabbits and further characterized the influence of positive end-expiratory pressure (PEEP). Forced oscillation tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…A previous study in normal BALB/c mice using closed versus open-chest measurements indicated that the chest wall contrib-uted~20% to G,~6% to R n , and did not affect H (53) while another study using C57BL/6 mice concluded that dynamic pulmonary mechanics in mice reflect only a minor contribution from the chest wall (28). However, a recent study on adult BALB/c mice reported that the chest wall may contributẽ 40% to G and~30% to H (55). There are no studies to date on the contribution of chest wall to respiratory mechanics in any model of OI.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in normal BALB/c mice using closed versus open-chest measurements indicated that the chest wall contrib-uted~20% to G,~6% to R n , and did not affect H (53) while another study using C57BL/6 mice concluded that dynamic pulmonary mechanics in mice reflect only a minor contribution from the chest wall (28). However, a recent study on adult BALB/c mice reported that the chest wall may contributẽ 40% to G and~30% to H (55). There are no studies to date on the contribution of chest wall to respiratory mechanics in any model of OI.…”
Section: Discussionmentioning
confidence: 99%
“…The classical parameters of respiratory mechanics, resistance, and compliance are related to the resistance of air in and out of the lungs as well as the expandability of the respiratory system. These measurements are based on the analysis of pressure, volume, and flow signals obtained from the oscillating airflow waveform applied to the airway opening of the subject [ 31 , 32 ]. Exposure to the silica increased respiratory resistance (Rrs), airway resistance (Rn), and tissue damping (G) in mice.…”
Section: Discussionmentioning
confidence: 99%
“…While Raw is mainly specific to the flow resistance of the conducting airways [ 49 ], the tissue parameters damping and elastance include not only pulmonary components but are also influenced by other structures of the total respiratory system, mainly the chest wall [ 49 ]. Previous literature attributed a chest wall contribution of approximately 30–50% to these parameters [ 50 ] and since the chest wall contribution is not expected to change after lung injury and mechanical ventilation [ 51 ], the observed changes are interpreted as being mainly of pulmonary origin. Therefore, the corresponding changes registered in tissue damping and elastance are predictably underestimating the real pulmonary changes.…”
Section: Discussionmentioning
confidence: 99%